The effectiveness of social media in helping business / Muhammad Harith Danish Mohd Khalid ...[et al.] - Mohd Khalid, Muhammad Harith Danish; Zakariya, Nursyafiqah Amirah; Shahidan, Muhammad Asyrani; Meor Fadzli, Meor Farhan (Faculty of Communication & Media Studies, 2021)
It has been established that social media helps a lot of businesses sell their products and services on the internet these days. It is also well known that companies can use a variety of social media platforms to apply for and advertise their products and services. People nowadays, for example, utilize Instagram, Facebook, Tiktok, and Twitter to market and advertise their items to locals. This study is about the activeness of social media in helping business. This study involves 260 respondents selected from a variegated race in Malaysia. A cross sectional survey and structured questionnaire were used for data collection. All variables measured through scale previously used by researchers. Result for the survey show Issues of social media towards business in Malaysia is high and People acceptance towards social media on helping businesses to grow in Malaysia is also high (M=4.43)